SISTEM INFORMASI PERUMDA AIR MINUM TIRTA BANGKA BERBASIS WEBSITE - Tirza Rosari (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
Perumda Air Minum Tirta Bangka is a Regional Owned Enterprise (BUMD) of Bangka Regency that provides clean water services to all its customers. The services provided to the community are still conventional, where people who want to apply for the installation of new connections and customers submit complaints can only go directly to the office on weekdays. Submission of information regarding the obstacles that cause air not to reach the customer's house is also ineffective so that the problem is rarely known by the customer. Based on the problems that have been described, a research will be carried out which aims to design a Webiste-Based Information System for Perumda Air Minum Tirta Bangka. Methods of data collection in this study using the method of observation and interviews. For the design method using the waterfall method, which consists of stages of analysis, design, code and testing. The existence of this information system, hope it can help service between customers and the company to making it easier for customers to get information, apply for new connections and submit complaints they experience.